Growth and Survival Rate of Juaro (Pangasius polyuranodon Blkr) on Different Stocking Density in the Recirculation System - Iskhak Martinus Silaban; Mulyadi '; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted from May to July 2015 in the laboratory of AquacultureTechnology Faculty of Fisheries and Marine Sciences, University of Riau. The aim of thisstudy was to determine the best stocking density for the growth and survival of fish juaro(Pangasus polyuranodon Blkr). The method used was experimental method by using acompletely randomized design with three treatments and three replications. The treatments inthis study were P1 (2 tails/72 liters of water), P2 (4 tails/72 liters of water), P3 (6 tails/72liters of water)The results showed thatfish rearing juaro using a 2-tailed / 72 liters of water, the rateof growth of the weight of the fish absolute highest juaro 7.03g, 1.16% daily growth rate with100% survival rate and the results of water quality measurements for the study is thetemperature 27-300C, 6.57 to 6.77 pH, dissolved oxygen (DO) from 4.5 to 6.5 ppm/l andammonia (NH3) is 0.015 ppm.Keywords: Solid stocking, maintenance, juaro (Pangasius polyuranodon Blkr)1. Student of the Faculty Fisheries and Marine Science University of Riau2. Lecturer of the Faculty Fisheries and Marine Science University of RiauPENDAHULUANBudidaya perikanan merupakansalah satu